Research Progress in Ferroptosis during Postmortem Aging of Muscle and Its Relationship with the Quality of Fresh Meat - HAO Danni, TU Xiaohang, GUO Shiyu, ZHU Yongzhi, WANG Daoying, XU Weimin, LI Pengpeng (Shipin Kexue)
Water-holding capacity, texture and color are important indicators of fresh meat quality. In China, drip loss and textural deterioration of fresh meat are critical problems in the meat industry, causing greater quality loss than that in developed countries. Recently, researchers have identified a series of potential biomarkers for the water-holding capacity and tenderness of meat and have studied the effect of cell apoptosis on meat tenderness. However, the relationship between ferroptosis and fresh meat quality has been researched little. After slaughter, the intramuscular environment alters and ferroptosis occurs, which is characterized by the accumulation of iron, an increase in lipid oxidation and disruption of redox equilibrium. These changes are closely related to meat quality. This paper reviews the characteristics, metabolic pathways and regulatory mechanisms of ferroptosis, and the crosslinks between ferroptosis and other modes of cell death. Moreover, it elaborates on how ferroptosis affects fresh meat quality through iron homeostasis imbalance, redox imbalance and lipoperoxidation. Overall, this review provides deeper insights into the mechanism of meat quality formation during postmortem aging.